2015
DOI: 10.18869/acadpub.shefa.3.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Accidents and Incidents of Injury Registered in Medical Centers Affiliated to Shahid Beheshti University of Medical Sciences

Abstract: The purpose of this study was to investigate injuries resulting from accidents and incidents referred to medical centers and hospitals of Shahid Beheshti University of Medical Sciences. Materials and Methods: This study is a cross-sectional study. The data of all injured patients admitted to hospitals of Shahid Beheshti University of Medical Sciences from March 2014 to March 2015 were reviewed. Accidents and injuries were categorized according to the tenth version of international classification of diseases. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This rate is higher than average rates of accidents in the provincial level (Central Province) and less than average rates of accidents in the national level [18].Therefore, Khomein city is one of the regions with a moderate risk of accidents. The results of this study showed that men (71%) are faced with the risk of accidents more likely than women; these results were consistent with study of Abdulvand et al [19] and Vafaei et al [16]. In addition, a higher incidence of high-risk behaviors in men was indicated, and also the more presence of men in daily life activities was reported.…”
Section: Discussionsupporting
confidence: 91%
“…This rate is higher than average rates of accidents in the provincial level (Central Province) and less than average rates of accidents in the national level [18].Therefore, Khomein city is one of the regions with a moderate risk of accidents. The results of this study showed that men (71%) are faced with the risk of accidents more likely than women; these results were consistent with study of Abdulvand et al [19] and Vafaei et al [16]. In addition, a higher incidence of high-risk behaviors in men was indicated, and also the more presence of men in daily life activities was reported.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, urban areas and areas outside the cities and villages had higher frequency of accidents. In the study of Rafeie et al, urban areas with 53% and also in study of Abdolvand et al urban areas with 96.3% of accidents had the highest number of accidents compared to other regions (11,12). According to the report of Legal Medicine Organization, the highest number of accidents each year occurs in September.…”
Section: Discussionmentioning
confidence: 80%
“…Souri et al reported the incidence of injuries and accidents in the age group of 20-25 years was higher than other age groups in Iran (10). Also in studies conducted in other provinces and cities of the country, the age group of 15-25 years and 25-35 years were the most vulnerable groups in terms of the number of accidents (11,12). In a study in Golestan province, 75.4% of accidents were in men (12).…”
Section: Discussionmentioning
confidence: 96%
“…More than 5 million people die each year worldwide due to accidents, which accounts for one-tenth of all deaths and causes tens of millions to refer to emergency medical centers. In addition to incurring high costs on the individuals and society, it causes temporary and permanent disabilities and loss of useful life [1]. One of the most critical dangers that threaten human life in different world countries is the increase in various accidents and related injuries [2].…”
Section: Introductionmentioning
confidence: 99%